Психодиагностика как научная основа деятельности практического психолога - Александр Федорович Ануфриев (Психология. Журнал Высшей школы экономики, 2011)
The author analyses the theory and methodology of psychodiagnostics and differentiates between psychodiagnostics as a kind of practice and as an academic discipline which underlines it. He distinguishes four components in the structure of the discipline and mentions main categories on which a practitioner draws while making a diagnosis. The author describes perspectives that the discipline of psychodiagnostics opens for psychological research and practice.